If , a = sqrt6 - sqrt3 b = sqrt3 - sqrt2 c = sqrt2 - sqrt6 , then find the value of a^3 + b^3 + c^3 - 2abc
[ Not a original question ]
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If in the expression a^3 + b^3 + c^3, a+ b+c=0 then a^3 + b^3 + c^3 = 3abc. Using this above we only have to solve a b c which is equal to 3sqrt2 - 4sqrt3 + sqrt6, and which is not time taking.😎